SURFACE MYCOFLORA OF STORED PART OF HERBAL MEDICINE - DHALE D. A. (International Journal of Pharma and Bio Sciences, 2013)
This investigation was designed to throw light on the mycoflora of some crude herbal materials. Randomly 15 different stored herbal medicines were brought to the laboratory from three different shops in Dhule City (M.S., India). The surface mycoflora associated with these samples was studied by standard methods of incubation - Blotter test, Agar plate test and Surface washing method. During the present investigations on herbal medicines, the high percentage of mycoflora observed in blotter test. Almost all the samples screened for the study were found to be contaminated with 44 species belonging to 15 genera of fungi. The samples were mixed with dust and debris, while contaminated contained maximum amount of soil particles. Their effect on patients consuming such contaminated medicines also calls for urgent attention. General cleanliness and hygienic habits in handling of herbal stocks, awareness of necessity for sterility will decreases risks of proliferating sickness will be minimized.